DISTINCTIVE FEATURES OF MALE AND FEMALE SPEECH - M. Muhammadova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article provides detailed information about the color of words used by men and women, who are the backbone and main link of society, and its role in society.